Igreja Universal e democracia no Brasil: uma abordagem sobre as transformações do fenômeno político contemporâneo - Antonio, Gabriel Henrique Burnatelli de (Universidade Federal de São Carlos, 2011)
This study sought to develop as its background theme the critical dimension of the contemporary political phenomenon, focusing on its impacts in Brazil´s democratization process. Starting from this agenda, the specific goal rested in the study of social and institutional conditions for the emergence of the Universal Church of the Kingdom of God (IURD) as a political subject in Brazilian democracy. With this issue, this study tried to point out that the large stock of individuals in social subaltern conditions, the weak democratic experiment in the Brazilian republican history and the historical absence of mechanisms to build social empowerment facilitated the emergence, in recent decades, of political interests such as presented by the data collected about it from IURD: eminently corporate, unconcerned with the public sphere and with the construction of a civic culture that could guide its social bases for the enjoyment of a well understood citizenship.
Keywords: Ciência política; Esfera pública; Democracia; Cultura política; Neopentecostalismo; CIENCIAS HUMANAS::CIENCIA POLITICA